Are Physical Activity and Sedentary Behavior Associated With Cancer-Related Symptoms in Real Time?: A Daily Diary Study. Issue 1 (5th January 2022) - Paxton, Raheem J.; Bui, Chuong; Fullwood, Dottington; Daniel, Danielle; Stolley, Melinda; Oliver, JoAnn S.; Wang, Kun; Dubay, John W.
Abstract : Background: Few studies have examined the real-time and dynamic relationship between lifestyle behaviors and treatment-related symptoms. Objective: The aim of this study was to examine the associations of daily physical activity and sedentary behavior with symptom burden, pain interference, and fatigue among patients who were undergoing active cancer treatment. Methods: A total of 22 (mean age = 57 years; 73% women; 55% Black) cancer patients were recruited from a local hospital and reported a daily diary of physical activity, sedentary behavior, symptom burden, pain interference, and fatigue over 10 days. Adjusted mixed-effects models were used to examine all associations. Results: Body mass index moderated the relationship between physical activity and symptom burden ( γ = 0.06, P < .01) and physical activity and fatigue ( γ = 0.09, P < .05). On days where physical activity was higher than average, symptom burden and fatigue scores were lower among patients who had lower body mass index values. Also, age moderated the relationship between sedentary behavior and symptom burden ( γ = −0.04, P < .05); on days where patients sat more, symptom burden was lower among patients who were younger than the average age. Conclusions: Overall, these data indicate that treatment-related symptoms vary daily within cancer patients and that physical activity may alleviate treatment-related symptoms for leaner patients. Larger samples and objective assessments of physical activity and sedentary behavior are needed to validate our results. Implications for Practice: Oncology nurses may be in the best position to promote physical activity during treatment as a strategy to manage symptom burden.